2017
DOI: 10.29328/journal.jsmt.1001006
|View full text |Cite
|
Sign up to set email alerts
|

3-Dimensional Versus 2-Dimensional Comparison of Knee Valgus Collapse during Vertical Jump: Clinical Implications for ACL Risk of Injury Assessment

Abstract: Time-effi cient screening of lower extremity biomechanics to identify potential injurious movement patterns is crucial within athletic medicine settings. When considering biomechanical risk factors for anterior cruciate ligament injuries, several screening tests have been used to assess dynamic knee valgus. Current methods involving 3-dimensional motion capture systems are considered gold standard for such assessment; however, these methods are time consuming and require expensive materials. This study investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…By advancing the understanding of how frontal plane measures generated by 3-dimensional motion capture systems correlate to the KAA, investigators may identify the selection of more promising frontal plane surrogates for future investigations. This notion is supported by Cesar et al, 10 who concluded that investigation using 3-dimensional motion analysis to generate correlations of 2-dimensional frontal measures is a first step to screen for aberrant movement patterns. Moreover, advances in depth camera sensors appear promising to address the space, cost, and technical limitations of traditional gait laboratories.…”
Section: Discussionmentioning
confidence: 81%
“…By advancing the understanding of how frontal plane measures generated by 3-dimensional motion capture systems correlate to the KAA, investigators may identify the selection of more promising frontal plane surrogates for future investigations. This notion is supported by Cesar et al, 10 who concluded that investigation using 3-dimensional motion analysis to generate correlations of 2-dimensional frontal measures is a first step to screen for aberrant movement patterns. Moreover, advances in depth camera sensors appear promising to address the space, cost, and technical limitations of traditional gait laboratories.…”
Section: Discussionmentioning
confidence: 81%
“…Although literature shows the importance of investigating knee biomechanics during athletic landing tasks for injury prevention [15,16], establishing the mechanism of injury is a step required prior to elaborating a prevention program [17]. Few are the studies contrasting knee biomechanics of the athletic population mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, previous research has not investigated the comparison of landing techniques in different sports, such as basketball and volleyball. Additionally, although the 2-dimensional approach can provide enough information regarding an initial screening for injurious movement patterns [16], a more robust (i.e., 3-dimensional) analysis is warranted for a comprehensive analysis of biomechanical demands around the knee joint between sports.…”
Section: Introductionmentioning
confidence: 99%